Strategi Inovatif Pengelolaan Sampah Rumah Tangga Perkotaan (Studi pada Bank Sampah â€œSri Wilisâ€ Perum Wilis II Kelurahan Pojok Kecamatan Mojoroto Kota Kediri) - Ayu Dewanti Anggraini (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2015)
Abstract : Urban Household Trash Management Innovative Strategy (Study of Bank Sampah â€œSri Wilisâ€ Perum Wilis II in Kelurahan Pojok, Kecamatan Mojoroto, Kota Kediri). Research in conducted to look at how far Bank Sampah â€œSri Wilisâ€ Kota Kediri can organize Household Trash Management. The activity is done by executing various innovative strategies in trash management, developing the value of trash, and socializing the impact of clean and healthy environment by increasing community participation. Result of research can be explained as follows: (1) Innovative strategy done by Bank Sampah â€œSri Wilisâ€ for house trash management is already mature. Community is empowered through socialization and trainings. Actors in this engagement include the government, the immediate citizens around Perum Wilis, outsider peoples, and some schools in Kota Kediri. To increase community participation, save-loan system is built. Economic factor is considered by such innovative strategy by givingeconomic added-value to the result of trash transaction; and (2) Some factors are influential. The suppoting factors are member participation, structure and infrastructure, participation of immediate community, and cooperation with Cleanliness and Gardening Official of Kota Kediri. The constraining factors include the unchanged mindset of community and the lack of readiness from the personnel to collect trashes from the households. Keyword : Innovative, Strategy, Household Trash Abstrak : Strategi Inovatif Pengelolaan Sampah Rumah Tangga Perkotaan (Studi pada Bank Sampah â€œSri Wilisâ€ II Kelurahan Pojok Kecamatan Mojoroto Kota Kediri). Penelitian ini dilakukan untuk dapat melihat bagaimana sejauh ini Bank Sampah â€œSri Wilisâ€ Kota Kediri dalam melaksanakan program yang telah diberikan untuk. Dari hasil penelitian yang telah dilakukan ini menunjukkan (1) strategi inovatif yang dilakukan Bank Sampah â€œSri Wilisâ€ telah dilaksanakan dengan maksimal. Pemberdayaan masyarakat yang telah dilakukan dengan cara sosialisasi dan berbagai pelatihan, Aktor yang terlibat didalamnya yaitu pemerintah, masyarakatÂ serta beberapa sekolah-sekolah di Kota Kediri. Upaya yang dilakukan dengan adanya simpan pinjam, serta faktor ekonomi yang didapat. Serta (2) faktor-faktor yang menjadi mempengaruhi, faktor pendukung dengan adanya keterlibatan anggota, masyarakat sekitar, adanya sarana dan prasarana dan kerjasama dengan DKP Kota Kediri. Faktor penghambat Â mindset beberapa masyarakat yang belum dapat berubah serta adanya ketidaksiapan anggota pengurus dalam mengambil sampah rumah tangga. Kata Kunci : Strategi, Inovatif, Sampah Rumah TanggaÂ